Availability, Quality, and Evidence-Based Content of mHealth Apps for the Treatment of Nonspecific Low Back Pain in the German Language: Systematic Assessment - Lauro Ulrich; Phillip Thies; Annika Schwarz (JMIR Publications, 2023)
BackgroundNonspecific low back pain (NSLBP) carries significant socioeconomic relevance and leads to substantial difficulties for those who are affected by it. The effectiveness of app-based treatments has been confirmed, and clinicians are recommended to use such interventions. As 88.8% of the German population uses smartphones, apps could support therapy. The available apps in mobile app stores are poorly regulated, and their quality can vary. Overviews of the availability and quality of mobile apps for Australia, Great Britain, and Spain have been compiled, but this has not yet been done for Germany. ObjectiveWe aimed to provide an overview of the availability and content-related quality of apps for the treatment of NSLBP in the German language. MethodsA systematic search for apps on iOS and Android was conducted on July 6, 2022, in the Apple App Store and Google Play Store. The inclusion and exclusion criteria were defined before the search. Apps in the German language that were available in both stores were eligible. To check for evidence, the apps found were assessed using checklists based on the German national guideline for NSLBP and the British equivalent of the National Institute for Health and Care Excellence. The quality of the apps was measured using the Mobile Application Rating Scale. To control potential inaccuracies, a second reviewer resurveyed the outcomes for 30% (3/8) of the apps and checked the inclusion and exclusion criteria for these apps. The outcomes, measured using the assessment tools, are presented in tables with descriptive statistics. Furthermore, the characteristics of the included apps were summarized. ResultsIn total, 8 apps were included for assessment. Features provided with different frequencies were exercise tracking of prefabricated or adaptable workout programs, educational aspects, artificial intelligence-based therapy or workout programs, and motion detection. All apps met some recommendations by the German national guideline and used forms of exercises as recommended by the National Institute for Health and Care Excellence guideline. The mean value of items rated as "Yes" was 5.75 (SD 2.71) out of 16. The best-rated app received an answer of "Yes" for 11 items. The mean Mobile Application Rating Scale quality score was 3.61 (SD 0.55). The highest mean score was obtained in "Section B-Functionality" (mean 3.81, SD 0.54). ConclusionsAvailable apps in the German language meet guideline recommendations and are mostly of acceptable or good quality. Their use as a therapy supplement could help promote the implementation of home-based exercise protocols. A new assessment tool to obtain ratings on apps for the treatment of NSLBP, combining aspects of quality and evidence-based best practices, could be useful. Trial RegistrationOpen Science Framework Registries sq435; https://osf.io/sq435